CdS incorporation induced gate-opening in UiO-66-NH2 for photocatalysis - Qi Li; Bryan Kit Yue Ng; Zhao-Xue Luan; Ping-Luen Baron Ho; Daniel Woodside; Xiyu Zhang; Christopher Foo; Pu Zhao; Tai-Sing Wu; Yun-Liang Soo; Mingjie Li; Xin-Ping Wu; et al. (Chemical Engineering Journal, 2026)

Understanding and managing species range shifts: first observed mixed-species outbreak and coral predation by crown-of-thorns starfish (Acanthaster brevispinus and A. cf. solaris) on subtropical reefs - Brigitte Sommer; Hamish A. Malcolm; Christopher Cooney; Steven J. Dalton; Shawna A. Foo; Nicola Fraser; Tsai-Hsuan Tony Hsu; David Maguire; Matt J. Nimbs; Nicole Strehling; Monique Webb; Maria Byrne (Marine Environmental Research, 2025)

Integrative epigenomic and transcriptomic analyses reveal metabolic switching by intermittent fasting in brain - Gavin Yong-Quan Ng; Dominic Paul Lee Kok Sheng; Han-Gyu Bae; Sung Wook Kang; David Yang-Wei Fann; Jinsu Park; Joonki Kim; Asfa Alli-Shaik; Jeongmi Lee; Eunae Kim; Sunyoung Park; Jeung-Whan Han; et al. (GeroScience, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Warming Alters the Relationship Between Benthic Cover and Herbivores on Hawaiian Reefs - Shawna A. Foo; Christopher H. Teague; Gregory P. Asner (Frontiers in Marine Science, 2022)
Increases in sea surface temperature impact animal metabolism, which in turn could influence benthic structure and resulting algal-coral balance. We utilized a long-term coral reef dataset from the west coast of Hawai‘i Island to investigate impacts of annual positive and negative sea surface temperature anomalies (SSTA) on benthic cover [algal turf, macroalgae, crustose coralline algae (CCA), and coral], herbivore density (sea urchins, grazers, browsers, and scrapers) and the relationship between benthic cover and herbivore density. Results showed significantly lower coral cover, but higher CCA cover with positive SSTA. Additionally, the density of sea urchins, grazers and browsers increased with increasing SSTA. Warming disrupted the normal relationship between herbivores and benthic cover on reefs, particularly for grazers where higher densities were coupled with lower algal turf cover only during negative SSTA. The direction of the relationship between benthic cover and herbivore type changed with positive SSTA, where increased algal turf cover was associated with increased herbivore density. Here, herbivores are likely responding accordingly to increases in food availability due to increased metabolism under warming. Despite herbivore populations increasing in density over the past two decades, algal turf cover remains on an upward trajectory. These results indicate that warming can alter herbivore-algal dynamics, where greater herbivore densities may be required to cause a reduction in algal turf cover. Protection of herbivores in addition to reducing nutrient input onto reefs will be essential in driving a reduction in algal turf cover on Hawaiian reefs.

Regional Reef Fish Survey Design and Scaling Using High-Resolution Mapping and Analysis - Gregory P. Asner; Nicholas Vaughn; Bryant W. Grady; Shawna A. Foo; Harish Anand; Rachel R. Carlson; Ethan Shafron; Christopher Teague; Roberta E. Martin (Frontiers in Marine Science, 2021)
Coral reefs are undergoing changes caused by coastal development, resource use, and climate change. The extent and rate of reef change demand robust and spatially explicit monitoring to support management and conservation decision-making. We developed and demonstrated an airborne-assisted approach to design and upscale field surveys of reef fish over an ecologically complex reef ecosystem along Hawai‘i Island. We also determined the minimal set of mapped variables, mapped reef strata, and field survey sites needed to meet three goals: (i) increase field survey efficiency, (ii) reduce field sampling costs, and (iii) ensure field sampling is geostatistically robust for upscaling to regional estimates of reef fish composition. Variability in reef habitat was best described by a combination of water depth, live coral and macroalgal cover, fine-scale reef rugosity, reef curvature, and latitude as a proxy for a regional climate-ecosystem gradient. In combination, these factors yielded 18 distinct reef habitats, or strata, throughout the study region, which subsequently required 117 field survey sites to quantify fish diversity and biomass with minimal uncertainty. The distribution of field sites was proportional to stratum size and the variation in benthic habitat properties within each stratum. Upscaled maps of reef survey data indicated that fish diversity is spatially more uniform than fish biomass, which was lowest in embayments and near land-based access points. Decreasing the number of field sites from 117 to 45 and 75 sites for diversity and biomass, respectively, resulted in a manageable increase of statistical uncertainty, but would still yield actionable trend data over time for the 60 km reef study region on Hawai‘i Island. Our findings suggest that high-resolution benthic mapping can be combined with stratified-random field sampling to generate spatially explicit estimates of fish diversity and biomass. Future expansions of the methodology can also incorporate temporal shifts in benthic composition to drive continuously evolving fish monitoring for sampling and upscaling. Doing so reduces field-based labor and costs while increasing the geostatistical power and ecological representativeness of field work.

Pilot sequencing of onion genomic DNA reveals fragments of transposable elements, low gene densities, and significant gene enrichment after methyl filtration - Jernej Jakše; Jenelle D. F. Meyer; Go Suzuki; John McCallum; Foo Cheung; Christopher D. Town; Michael J. Havey (Molecular Genetics and Genomics, 2008)

Comparative sequence and genetic analyses of asparagus BACs reveal no microsynteny with onion or rice - Jernej Jakše; Alexa Telgmann; Christian Jung; Anil Khar; Sergio Melgar; Foo Cheung; Christopher D. Town; Michael J. Havey (Theoretical and Applied Genetics, 2006)